Labour characteristics of women achieving successful vaginal birth after caesarean section in three European countries. (July 2019) - Grylka-Baeschlin, Susanne; Clarke, Mike; Begley, Cecily; Daly, Deirdre; Healy, Patricia; Nicoletti, Jane; Devane, Declan; Morano, Sandra; Krause, Gérard; Karch, André; Savage, Gerard; Gross, Mechthild M.
Abstract: Objective: Knowledge about labour characteristics of women achieving successful vaginal birth after caesarean section (VBAC) might be used to improve labour and birth management. This study examined sociodemographic and labour process-related factors regarding a) differences between countries, b) the comparison of successful VBAC with unplanned caesarean section, and c) predictors for the success of planned VBAC in three European countries. Design: We analysed observational data collected within the OptiBIRTH trial, a cluster-randomised controlled trial. Setting: Fifteen study sites in Ireland, Italy and Germany, five in each country. Participants: 790 participants going into labour for planned VBAC. Measurements: Descriptive statistics and random-effects logistic regression models were applied. Findings: The pooled successful VBAC-rate was 74.6%. Italy had the highest proportion of women receiving none of the four intrapartum interventions amniotomy (ARM), oxytocin, epidural or opioids (42.5% vs Ireland: 26.8% and Germany: 25.3%, p < 0.001). Earlier performance of ARM was associated with successful VBAC (3.50 hrs vs 6.08 hrs, p  = 0.004). A positive predictor for successful vaginal birth was a previous vaginal birth (OR=3.73, 95% CI [2.17, 6.44], p < 0.001). The effect of ARM increased with longer labour duration (OR for interaction term=1.06, 95% CI [1.004, 1.12], p  = 0.035). Higher infant birthweight (OR per kg=0.34, 95% CI [0.23, 0.50], p < 0.001), ARM (reference spontaneous rupture of membranes (SROM), OR=0.20, 95% CI [0.11, 0.37], p < 0.001) and a longer labour duration (OR per hour=0.93, 95% CI [0.90, 0.97], p < 0.001) decreased the odds of a vaginal birth. Key conclusion: Women with a previous vaginal birth, an infant with a lower birth weight, SROM and a shorter labour duration were most likely to have a successful vaginal birth. If SROM did not occur, an earlier ARM increased the odds of a vaginal birth. Implication for practice: Labour progress should be accelerated by fostering endogenous uterine contractions. With slow labour progress and intact membranes, ARM might increase the chance of a vaginal birth.